2004
DOI: 10.1051/0004-6361:20041298
|View full text |Cite
|
Sign up to set email alerts
|

Collimated molecular jets from high-mass young stars: IRAS 18151-1208

Abstract: Abstract. Recent near-IR images of massive star forming regions have revealed two collimated jets in the IRAS 18151-1208 region, one of which is almost a parsec in length (Varricatt et al.). Follow-up high-spectral-resolution echelle spectroscopy and 2-dimensional "integral field" spectroscopy of the associated molecular shock features are presented here. From these data kinematic information and excitation maps are extracted, which show that the two jets are morphologically, kinematically and energetically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 55 publications
(70 reference statements)
8
97
1
1
Order By: Relevance
“…They are very similar to those measured in other high-mass protostellar jets (10 18 -10 19 cm −2 ) (see e.g. Davis et al 2004;Gredel 2006), and they are 1-2 orders of magnitude higher than the values observed in low-mass jets.…”
Section: Ro-vibrational Diagrams From Nir Linessupporting
confidence: 87%
See 1 more Smart Citation
“…They are very similar to those measured in other high-mass protostellar jets (10 18 -10 19 cm −2 ) (see e.g. Davis et al 2004;Gredel 2006), and they are 1-2 orders of magnitude higher than the values observed in low-mass jets.…”
Section: Ro-vibrational Diagrams From Nir Linessupporting
confidence: 87%
“…By varying the extinction value (A v ) and increasing the goodness of the fit (maximising the correlation coefficient), extinction and temperature can be evaluated simultaneously (see e.g. Giannini et al 2004;Davis et al 2004;Caratti o Garatti et al 2006). To reduce the uncertainties, only the transitions with S /N > 3 and not affected by blending with other lines were used.…”
Section: Ro-vibrational Diagrams From Nir Linesmentioning
confidence: 99%
“…However, if one plots column densities derived from lines from only the first few vibrational states, a linear fit is usually quite adequate (e.g. Lorenzetti et al 2002;Giannini et al 2004;Davis et al 2004;Gredel 2006;Caratti o Garatti et al 2008;Martín-Hernández et al 2008). By minimising the scatter of points about this line, one can then estimate the extinction.…”
Section: Appendix A: the Effects Of Differential Refraction On Sourcementioning
confidence: 99%
“…Although the calculated momentum rate in the SiO jet is adequate to power the CO flow, the uncertainties in the assumed SiO abundance makes this difficult to prove. Another example is IRAS 18151-1208 in which the H 2 jet appears to have adequate momentum to power the observed CO flow (Beuther et al 2002a, Davis et al 2004. For sources that have a weak jet component coupled with a wide-angle flow, it has not been determined what fraction of the momentum rate is supplied by the jet.…”
Section: Outflow Energeticsmentioning
confidence: 99%